Penyidikan Tindak Pidana Penyelundupan Manusia Oleh Direktorat Reserse Kriminal Umum Polisi Daerah Riau - Aulia Rahma; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
People smuggling occurred in the city of Pekanbaru, this is because Pekanbaru a place where the border regions directly adjacent to some neighboring countries. Such as Malaysia and Singapore, so it becomes a shortcut or transit for people smuggling. people smuggling that occurred during this the Regional Police Pekanbaru city. The Regional Police Pekanbaru city in 2013 that managed to arrest two suspects and took fourteen foreign nationals who comes from Afganistan and Pakistan, in 2014 that managed to arrest five suspects and took twenty one foreign nationals who comes from Afganistan and Pakistan more. In 2015 that took twenty six foreign nationals who come from Afganistan and Myanmar.Who comes from the land.This type of research is quite sociological research, because in this study the autors directly conduct research on location or places studied in order to give a complete and clear picture of problems examined. This research was conducted at the Regional Police in Pekanbaru, while the sample population is a whole party with regard to the issues examined in the study. The source of the data used primary data and secondary data, while data collecting technique in this research is done with interviews and study data using deductive method is to analyze the problems of general nature subsequently with drawn padfa specific conclusion basic on existing theories.Result of the research this paper is : first, Invistigation of the crime people smuggling in the region Pekanbaru town in handling the Regional Police is not yet optimal, secondly, cost constraints, the infrastructure facilities, the victim, the lack of public knowledge about the crime of people smuggling, and the need translator for their investigation process, third efforts in dealing with the crime of people smuggling is effective and efficient in handling criminal cases of people smuggling with doing additional costs, complementary facilities and infrastructure, protection of victims, made approaches to community related dangers the crime of people smuggling, and the need for translator for investigation the crime of people smuggling.Key words : Invistigation-People Smuggling-Victim